Goal-directed therapy to maintain haemostasis. Issue 2 (June 2016) - Oscier, C.; Cecconi, M.
Abstract : Perioperative goal-directed therapy typically involves the use of haemodynamic targets to optimise oxygen delivery. Common goals include stroke volume, cardiac output and arterial blood pressure, although future protocols may also incorporate an assessment of vascular tone and the microcirculation. This article reviews the current evidence for goal-directed therapy and discusses future directions.